УДОСКОНАЛЕННЯ АЛГОРИТМУ ВИЗНАЧЕННЯ ВПЛИВУ ТЕМПЕРАТУРИ ПОВІТРЯ НА СУМАРНЕ ЕЛЕКТРИЧНЕ НАВАНТАЖЕННЯ ЕНЕРГОСИСТЕМИ ДЛЯ ПІДВИЩЕННЯ ТОЧНОСТІ КОРОТКОСТРОКОВОГО ПРОГНОЗУВАННЯ - Черненко, П.О.; Сичова, В.В. (Інститут електродинаміки НАН України, Київ, 2021)
Based on the research, the article presents three algorithms that allow to select from the overall electrical load (OEL) of the power system technological and temperature components in each hour of the daily schedule, which provides greater accuracy of short-term forecasting (STF) OEL of the power system. Calculations by three algorithms were performed according to Kyivenerho. The analysis of reading temperature sensors on four sources from the point of view of possibility of their application at STF is carried out. References 6, figures 3, tables 3.